PENINGKATKAN KOMPETENSI KEPRIBADIAN GURU DALAM MENGEMBANGKAN AKHLAK MULIA PESERTA DIDIK MELALUI PENANAMAN NILAI-NILAI KARAKTER BUDAYA JAWA - Nurkhan Nurkhan (Counsellia: Jurnal Bimbingan dan Konseling, 2015)
Objective is to be achieved in this study was to determine the success of plantingvalues-based character of Javanese culture in improving personal competence ofteachers, research was conducted in Dabin Sudirman is in SD 1Bulungcangkring. To determine the success of the study, the researchers gave thepretest and reflection, reflection in cycle 1 and 2. The purpose of the pretest wasto determine the initial condition of personal competence of teachers, while thereflection 1 and 2 is intended to determine the success of the action, whether theaction is implemented there is increasing? what does not. in addition to validatingthe results of the study, researchers using observation data and observations thathave been analyzed, the data will be used for the development of more lanjut.Daridata analysis proved that there is an increase in the average score rose 24.9points from the value of the pretest or 12 , 44%.